The Adobe Photoshop Lightroom 5 book : the complete guide for photographers - Evening, Martin (Adobe Press, 2013)
Adobe Photoshop Lightroom was designed from the ground up with digital photographers in mind, offering powerful editing features in a streamlined interface that lets photographers import, sort, and organize images. In this completely updated bestseller, author Martin Evening describes features in Lightroom 5 in detail from a photographer's perspective. As an established commercial and fashion photographer, Martin knows firsthand what photographers need for an efficient workflow. He has been working with Lightroom from the beginning, monitoring the product's development and providing valued feedback to Adobe. As a result, Martin knows the software inside and out, from image selection to image editing and image management. In this book he'll teach you how to: Work efficiently with images shot in raw or JPEG formats Import photographs with ease and sort them according to your workflow Create and manage a personal image and video library Quickly apply tonal adjustments to multiple images Integrate Lightroom with Adobe Photoshop Export images for print or Web as digital contact sheets or personal portfolios Make the most of new features in Lightroom 5, such as extended spot removal, Upright corrections, and Smart Previews Photographers will find Lightroom 5 - and The Adobe Photoshop Lightroom 5 Book - indispensable tools in their digital darkrooms. "With Martin's expert guidance, you'll soon find that you have precisely the tools you need to turn your concentration back where it belongs - on making better pictures!" - George Jardine, digital photography consultant "As a photographer himself, Martin Evening knows what tools photographers need to realize their creative vision. In this book, he shows not only how Adobe Photoshop Lightroom works but also why it will become an essential part of any photographer's workflow." - Greg Gorman, photographer.